Noncanonical function of the Sex lethal gene controls the protogyny phenotype in Drosophila melanogaster. - Seong, K.H.; Kang, S. (Scientific reports, 2022)
Drosophila melanogaster females eclose on average 4 h faster than males owing to sexual differences in the pupal period, referred to as the protogyny phenotype. Here, to elucidate the mechanism underlying the protogyny phenotype, we used our newly developed Drosophila Individual Activity Monitoring and Detecting System (DIAMonDS) that detects the precise timing of both pupariation and eclosion in individual flies. Although sex transformation induced by tra-2, tra alteration, or msl-2 knockdown-mediated disruption of dosage compensation showed no effect on the protogyny phenotype, stage-specific whole-body knockdown and mutation of the Drosophila master sex switch gene, Sxl, was found to disrupt the protogyny phenotype. Thus, Sxl establishes the protogyny phenotype through a noncanonical pathway in D. melanogaster.